VEGF-C expression is not a prognostic factor in locally advanced colon adenocarcinoma - Szajewski, Mariusz; Janusz Kruszewski, Wiesław; Lakomy, Joanna; Ciesielski, Maciej; Kawecki, Krzysztof; Szefel, Jarosław (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Evaluation of the relationships between increased expression of VEGF-C (vascular endothelial growth factor-C) and vessel density in the tumour-surrounding stroma, patient survival, and other conventional prognostic factors in patients with pT3-4 colon cancer. Material and methods: Expression of VEGF-C and vessel density were immunohistochemically assessed in 104 specimens of primary, locally advanced (pT3-4) colon adenocarcinoma after surgical resection. Results : A significant relationship was found between the expression of VEGF-C and increased vessel density in the tumour-surrounding stroma (p = 0.03). A relationship between VEGF-C expression and location of the tumour in the left side of the colon was also found (p = 0.003). Expression of VEGF-C was likely to occur in well-differentiated tumours. No relationship between patient overall survival and the expression level of VEGF-C in locally advanced colon cancer was observed. Conclusions : The study results indicate that expression of VEGF-C in cells of locally advanced pT3-4 adenocarcinoma of the colon does not affect the survival time of the patients. Increased expression of VEGF-C is accompanied by a significant increase in vessel density in the pT3-4 tumour stroma. Increased expression of VEGF-C in cancer cells is related to the tumour location in the left side of the colon and better tumour differentiation.